Institutions and Firms' Return to Innovation : Evidence from the World Bank Enterprise Survey - Nguyen, Ha; Jaramillo, Patricio A. (World Bank, Washington, DC, 2014)
This paper poses a question: do firms in developing countries not innovate because they are unwilling to? The question moves away from the conventional focus on the obstacles (such as the lack of access to finance) that hinder firms' innovation ability. The World Bank's Enterprise Survey is used first to estimate the return to firms' innovation across many developing countries, in terms of sales and sales per worker. Then the return to innovation is compared across countries with different levels of institutional quality. In countries with lower institutional quality (specifically, rule of law, regulatory quality, property and patent right protection), the return to firms' innovation is lower. This suggests that poor institutional environment lowers firms' return to innovation and hence discourages them from investing in researching and adopting new products.